Spectrophotometric determination of gentamicin loaded PLGA microparticles and method validation via ninhydrin-gentamicin complex as a rapid quantification approach - Harun @ Ismail, Ahmad Fahmi; Mohamed, Farahidah; Mohd Rosli, Luqman Muizzudin; Mohd Shafri, Mohd Affendi; Haris @ Harith, Muhammad Salahuddin; Adina, Anugerah Budipratama (Journal of Applied Pharmaceutical Science (http://www.japsonline.com), 2016)
The purpose of this study was to provide a quantification method with rapid, sensitive, reproducible and cost effective for gentamicin in the form of ninhydrin-gentamicin complex. The utilization of spectrophotometric module to validate the method development for gentamicin loaded microparticles was intended to provide alternative quantification method without undermining the sensitivity of the developed method. The microparticles fabrication process was proven to be suitable in encapsulating gentamicin by using poly(lactic-coglycolic acid) PLGA without compromising the efficacy of the antibiotic itself. The linearity of 6 known concentrations of ninhydrin-gentamicin complex was obtained with the R2 of 0.9998. The interday and intraday precisions were determined with the acceptance %RSD values of less than 2%. The highest %RSD value was 1.09% which suggested the method to be acceptably precise. The limit of detection (LOD) and limit of quantification (LOQ) values were recorded to be at 0.016 and 0.196 mg/mL respectively. The % recovery of 4 known concentrations indicated the accuracy of the method was high with the recovery range between 98.66% and 101.8%. The parameters analyzed in this study were in accordance with ICH Q2 (R1) guidelines. This quantification method was a promising approach to provide a rapid and cost effective in evaluating gentamicin concentration for in-vitro applications.